The Suppression Head Impulse Paradigm in Clinical Vestibular Testing: An Interpretation-Focused Narrative Review - Leonardo Manzari (The Journal of International Advanced Otology, 2026)
Suppression head impulse test (SHIMP) is a video head impulse test paradigm in which the visual target is head-fixed. Because the head impulse stimulus is identical to the conventional head impulse paradigm (HIMP; earth-fixed target), the 2 paradigms provide complementary information: HIMP primarily reveals vestibular hypofunction through compensatory catch-up saccades, whereas SHIMP elicits post-impulse anti-compensatory “recapture” saccades in healthy individuals and can therefore highlight residual vestibular drive and the integrity of the vestibulo-saccadic interaction. Since its first clinical description, SHIMP has been applied across unilateral and bilateral vestibular disorders and, more recently, in selected central nervous system conditions. However, interpretation remains variable between laboratories and devices and can be confounded by predictable stimulation, early saccades, covert substitution strategies, and phase-dependent changes after acute vestibular loss. This narrative review focuses on an interpretation framework that explicitly separates (i) vestibular drive (slow-phase vestibulo-ocular reflex and gain) from (ii) the saccadic strategy required to re-foveate the task-defined target. The review synthesizes the physiological rationale for the reversed saccadic signature of SHIMP versus HIMP, proposes a terminology set, and provides practical interpretation rules with key sub-cases (acute versus follow-up unilateral vestibular loss; bilateral vestibulopathy with “inappropriate” covert saccades; SHIMP-negative patterns with functional gain in central disorders). Emphasis is placed on trace-level waveform inspection and longitudinal, context-aware reading of gain and saccade metrics.